2011
DOI: 10.1364/oe.19.008847
|View full text |Cite
|
Sign up to set email alerts
|

Optical tweezers based active microrheology of sodium polystyrene sulfonate (NaPSS)

Abstract: We used oscillatory optical tweezers to investigate the microrheological properties of Sodium polystyrene sulfonate (NaPSS; Mw = 70 kDa) polymer solutions with different concentrations from 0.001 mM to 10 mM in terms of elastic modulus G'(ω) and loss modulus G"(ω) as a function of angular frequency (ω) in the range of 6 rad/s to 6000 rad/s. The viscoelastic properties (including zero-shear-rate viscosity, crossing frequency and transition frequency) as a function of polymer concentration, deduced from our prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Active microrheology refers to the determination of the material's viscoelasticity by recording motion of the test samples or of particles attached to the test samples in response to an external force. 3 In 2001, Jacobson et al 9 used atomic force microscopy (AFM) to measure the cortical stiffness during cell division, and reported that the elasticity of the cortex increased from 1.7 AE 0.9 to 3.9 AE 2.5 and 10.1 AE 5.5 (10 3 Pa), respectively, as the cleavage furrow contracted while Potorous tridactylus kidney cells divided from the metaphase through anaphase to telophase. Shimamoto et al 10 also used AFM to examine the dynamic viscoelasticity of microtubules and spindles in metaphase and reported that spindle viscosity could be related to microtubule density and cross-linking, and spindle elasticity to microtubule rigidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active microrheology refers to the determination of the material's viscoelasticity by recording motion of the test samples or of particles attached to the test samples in response to an external force. 3 In 2001, Jacobson et al 9 used atomic force microscopy (AFM) to measure the cortical stiffness during cell division, and reported that the elasticity of the cortex increased from 1.7 AE 0.9 to 3.9 AE 2.5 and 10.1 AE 5.5 (10 3 Pa), respectively, as the cleavage furrow contracted while Potorous tridactylus kidney cells divided from the metaphase through anaphase to telophase. Shimamoto et al 10 also used AFM to examine the dynamic viscoelasticity of microtubules and spindles in metaphase and reported that spindle viscosity could be related to microtubule density and cross-linking, and spindle elasticity to microtubule rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,[11][12][13] In an equilibrium system where only thermal forces act on the probe-particle, motion of the particle is the random walk of the particle caused by thermal fluctuations and collisions with surrounding molecules. It is sensitive not only to the temperature but also to the viscoelasticity of the surrounding material, and particle-tracking microrheology (based on Brownian motion) has been established as a convenient technique to measure the viscoelasticity of complex fluids, especially when the sample is available only in relatively small volumes on the order of a fraction of a microliter 3,6,11-13 such that conventional (classical) rheometers are not applicable.…”
Section: Introductionmentioning
confidence: 99%
“…Particles were first trapped in a strongly focused laser beam in the 1980s 12. Since then, optical trapping has found many applications in molecular biology, biophysics, and medicine, ranging from active microrheology in biopolymer networks13 to manipulation of biological molecules14 and DNA 15. 16 Information about the mechanical properties of these systems can be gathered by the use of small tracer particles 17.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Pcs bearing a crown ether group are present in an aqueous NaCl solution only as aggregates of uncertain composition or even as unstable suspension. [6,13] In the presence of strong polyelectrolyte PSS (cmc equal to 1.8•10 -4 М was reported), [14,15] an increase of the absorbance of the Mgcr 8 Pc solution is accompanied by noticeable changes of the Q-band shape relative to an aqueous solution of Pc (Figure 2b). The observed increase of the absorbance can be due to a decrease in the number of highly aggregated Mgcr 8 Pc particles.…”
Section: Resultsmentioning
confidence: 85%